2014
DOI: 10.1016/j.jtcvs.2014.05.089
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of pulmonary arterial branch sealing using energy devices in an ex vivo model

Abstract: In this pilot study to examine energy sealing of PA branches in a simulated ex vivo model, vascular sealing using energy was effective and was able to sustain high intraluminal bursting pressures. Further research is needed to determine the in vivo and long-term safety of PA branch energy sealing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 24 publications
(40 reference statements)
1
22
0
Order By: Relevance
“…This device allows for controlled vascular pressurization with precise monitoring of pressure inflection and burst pressures (BPs) and was developed and tested specifically for this research program. This pressurization device has been previously described [4]. All pressure measurements were recorded and graphed related to the time from the initial vascular pressurization to PA BP.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This device allows for controlled vascular pressurization with precise monitoring of pressure inflection and burst pressures (BPs) and was developed and tested specifically for this research program. This pressurization device has been previously described [4]. All pressure measurements were recorded and graphed related to the time from the initial vascular pressurization to PA BP.…”
Section: Methodsmentioning
confidence: 99%
“…Sealing devices that use ultrasonic energy are effective and safe in sealing systemic arteries up to 7 mm [3]. The use of ultrasonic energy sealing for the PA has recently been evaluated [4]. We evaluated the immediate efficacy of an ultrasonic energy vessel-sealing device for sealing PA branches and compared it with the gold standard (endostapler) in an ex vivo PA sealing model.…”
mentioning
confidence: 99%
“…Liberman et al (33) evaluated four different energy sealing devices in pulmonary arterial branch sealing in an ex vivo model. This study suggested that ultrasound sealing technology seems to be superior to advanced bipolar technology in sealing pulmonary artery branches.…”
Section: Energy Devices In Vatsmentioning
confidence: 99%
“…Open and endosurgical stapling devices have become the standard instruments for closing the large pulmonary vessels [6], whereas the small pulmonary vessels are manually ligated with a suture or divided using a vessel-sealing device (VSD). Advanced bipolar and ultrasound technologies are still being evaluated in various trials [7][8][9]. Safe division of the pulmonary vessels, especially the pulmonary artery (PA), during anatomical lung resection, is critically important.…”
Section: Introductionmentioning
confidence: 99%